Eimeria tenella ROP kinase EtROP1 induces G0/G1 cell cycle arrest and inhibits host cell apoptosis. (24th April 2019) - Diallo, Mamadou Amadou; Sausset, Alix; Gnahoui‐David, Audrey; Silva, Adeline Ribeiro E.; Brionne, Aurélien; Le Vern, Yves; Bussière, Françoise I.; Tottey, Julie; Lacroix‐Lamandé, Sonia; Laurent, Fabrice; Silvestre, Anne
Abstract: Coccidia are obligate intracellular protozoan parasites responsible for human and veterinary diseases. Eimeria tenella, the aetiologic agent of caecal coccidiosis, is a major pathogen of chickens. In Toxoplasma gondii, some kinases from the rhoptry compartment (ROP) are key virulence factors. ROP kinases hijack and modulate many cellular functions and pathways, allowing T. gondii survival and development. E. tenella 's kinome comprises 28 putative members of the ROP kinase family; most of them are predicted, as pseudokinases and their functions have never been characterised. One of the predicted kinase, EtROP1, was identified in the rhoptry proteome of E. tenella sporozoites. Here, we demonstrated that EtROP1 is active, and the N‐terminal extension is necessary for its catalytic kinase activity. Ectopic expression of EtROP1 followed by co‐immunoprecipitation identified cellular p53 as EtROP1 partner. Further characterisation confirmed the interaction and the phosphorylation of p53 by EtROP1. E. tenella infection or overexpression of EtROP1 resulted both in inhibition of host cell apoptosis and G0/G1 cell cycle arrest. This work functionally described the first ROP kinase from E. tenella and its noncanonical structure. Our study provides the first mechanistic insight into host cell apoptosis inhibition by E. tenella . EtROP1 appears as a new candidate for coccidiosis control.